Utilization of Gamification-Based Media in an Effort to Make Learning Fun and Change the Mindset of Parents About the Importance of Children's Education - Rahayu, Wening Patmi; Hidayat, Rachmad (International Journal of Social Science and Community Service, 2024)
The use of technological and informational developments in education today needs to be implemented selectively. This selective approach aims to make educational activities more meaningful and help achieve desired learning goals. One such technological development is the utilization of gamification-based learning media. Gamification media is designed to be engaging, combining games with educational content. This approach benefits students during learning activities, as they remain engaged and understand the material better. In this context, parental involvement in children's education is equally important in supporting the development of learning activities. Community service activities integrated into learning programs help maintain quality standards and positively impact educational outcomes. Quality education, in turn, helps create quality human resources. Teachers can effectively utilize gamification media to enhance their lesson material. The success of these community service activities represents one approach to improving the distribution of quality education for all.